1990
DOI: 10.1182/blood.v75.10.1947.bloodjournal75101947
|View full text |Cite
|
Sign up to set email alerts
|

Direct demonstration of elevated aldehyde dehydrogenase in human hematopoietic progenitor cells

Abstract: Relative levels of cytoplasmic aldehyde dehydrogenase (ALDH) were determined in selected subpopulations of normal human bone marrow cells using a flow cytometric assay that simultaneously detects a cell surface antigen (as a marker of cell lineage and developmental stage) and the level of ALDH. The intracellular level of this enzyme has been shown to be directly related to cellular resistance to activated cyclophosphamide and is believed to be important in the survival of cells capable of repopulating marrow i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 0 publications
2
39
0
1
Order By: Relevance
“…Recent studies have shown that several stem cell types, including hematopoietic stem cells and neural stem cells, possess high ALDH activity. (15) Moreover, ALDH is upregulated in several types of CSC. (27,28) Therefore, ALDH has been used as a stem cell marker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that several stem cell types, including hematopoietic stem cells and neural stem cells, possess high ALDH activity. (15) Moreover, ALDH is upregulated in several types of CSC. (27,28) Therefore, ALDH has been used as a stem cell marker.…”
Section: Discussionmentioning
confidence: 99%
“…(14) We also focused on ALDH, another stem cell marker, that plays a key role in aldehyde metabolism. Several stem cell types, including hematopoietic stem cells (15) and neural stem cells, (16) possess high ALDH activities. We found that ALDH was upregulated in TEC compared with that in NEC.…”
mentioning
confidence: 99%
“…One promising strategy is to identify HSC and progenitors based on an enzymatic activity that is expressed at relatively high levels in primitive haematopoietic cells. A variety of studies using immunohistochemical and enzymatic assays have demonstrated that aldehyde dehydrogenase (ALDH) is highly expressed in primitive haematopoietic cells, suggesting that this enzyme may be a useful target for identifying HSC and progenitors (Kohn & Sladek, 1985;Sahovic et al, 1988;Kastan et al, 1990;Jones et al, 1995Jones et al, , 1996Niederreither et al, 1999). In support of this, Jones et al (1996) demonstrated that primitive murine bone marrow cells that expressed high levels of ALDH could be enriched using a fluorescent substrate of ALDH, termed dansyl-aminoacetaldehyde.…”
Section: Discussionmentioning
confidence: 99%
“…11 ALDH br cells comprise 0.5% to 5% of nucleated cells in human umbilical cord blood, cytokine-mobilized (eg, G-CSF) peripheral blood stem cells, and bone marrow, and they are highly enriched for stem and progenitor cells of multiple lineages. [11][12][13][14] Early work on ALDH br cells focused on bone marrow and umbilical cord blood hematopoietic lineages. ALDH br cells have high hematopoietic progenitor activity, and their key attributes are their ability to establish long-term, multilineage hematopoietic colonies and to engraft long term.…”
Section: Aldh Br Cellsmentioning
confidence: 99%